Sterol-Sensing Domain (SSD)-Containing Proteins in Sterol Auxotrophic Phytophthora capsici Mediate Sterol Signaling and Play a Role in Asexual Reproduction and Pathogenicity - Weizhen Wang; Zhaolin Xue; Linfang Xie; Xin Zhou; Fan Zhang; Sicong Zhang; Francine Govers; Xili Liu (Microbiology Spectrum, 2023)
ABSTRACT Phytophthora species are devastating filamentous plant pathogens that belong to oomycetes, a group of microorganisms similar to fungi in morphology but phylogenetically distinct. They are sterol auxotrophic, but nevertheless exploit exogenous sterols for growth and development. However, as for now the mechanisms underlying sterol utilization in Phytophthora are unknown. In this study, we identified four genes in Phytophthora capsici that encode proteins containing a sterol-sensing domain (SSD), a protein domain of around 180 amino acids comprising five transmembrane segments and known to feature in sterol signaling in animals. Using a modified CRISPR/Cas9 system, we successfully knocked out the four genes named PcSCP1 to PcSCP4 (for P. capsici SSD-containing protein 1 to 4), either individually or sequentially, thereby creating single, double, triple, and quadruple knockout transformants. Results showed that knocking out just one of the four PcSCPs was not sufficient to block sterol signaling. However, the quadruple “all-four” PcSCPs knockout transformants no longer responded to sterol treatment in asexual reproduction, in contrast to wild-type P. capsici that produced zoospores under sterol treatment. Apparently, the four PcSCPs play a key role in sterol signaling in P. capsici with functional redundancy. Transcriptome analysis indicated that the expression of a subset of genes is regulated by exogenous sterols via PcSCPs. Further investigations showed that sterols could stimulate zoospore differentiation via PcSCPs by controlling actin-mediated membrane trafficking. Moreover, the pathogenicity of the “all-four” PcSCPs knockout transformants was significantly decreased and many pathogenicity related genes were downregulated, implying that PcSCPs also contribute to plant-pathogen interaction. IMPORTANCE Phytophthora is an important genus of oomycetes that comprises many destructive plant pathogens. Due to the incompleteness of the sterol synthesis pathway, Phytophthora spp. do not possess the ability to produce sterols. Therefore, these sterol auxotrophic oomycetes need to recruit sterols from the environment such as host plants to support growth and development, which seems crucial during pathogen-plant interactions. However, the mechanisms underlying sterol utilization by Phytophthora spp. remain largely unknown. Here, we show that a family of sterol-sensing domain-containing proteins (SCPs) consisting of four members in P. capsici plays a key role in sterol signaling with functional redundancy. Moreover, these SCPs play a role in different biological processes, including asexual reproduction and pathogenicity. Our study overall revealed the multiple functions of PcSCPs and addressed the question of how exogenous sterols regulate the development of heterothallic Phytophthora spp. via SSD-containing proteins.